2007
DOI: 10.1097/ajp.0b013e31802b4f95
|View full text |Cite
|
Sign up to set email alerts
|

Urine Toxicology Screening Among Chronic Pain Patients on Opioid Therapy: Frequency and Predictability of Abnormal Findings

Abstract: These results confirm past findings that random urine toxicology screens among patients prescribed opioids for pain reveal a high incidence of abnormal findings. Common patient descriptors, and number, type, and dose of prescribed opioids were found to be poor predictors of abnormal results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
138
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 167 publications
(149 citation statements)
references
References 23 publications
7
138
4
Order By: Relevance
“…44 Our hypothesis that males would have more illicit drug results was not confirmed; findings in previous studies were mixed. 16,18 Consistent with prior studies, 18,20 we found no significant association between opioid regimen characteristics and illicit drugs.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…44 Our hypothesis that males would have more illicit drug results was not confirmed; findings in previous studies were mixed. 16,18 Consistent with prior studies, 18,20 we found no significant association between opioid regimen characteristics and illicit drugs.…”
Section: Discussionsupporting
confidence: 90%
“…Most prior studies focused only on predictors of illicit drug detection and included THC with other illicit drugs. [16][17][18][19] Our findings confirm the importance of younger age, SUD history, and smoking as risks for aberrancies, and reveal that risk factors vary across aberrancy types. In this setting, male gender predicted only THC detection; furthermore, history of mental health and alcohol use disorders (at least in the past two years) generally did not predict aberrancies.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations